Prevalence and transmission of HIV-1 drug resistance mutations among patients with treatment failure and newly diagnosed people in Liangshan Prefecture, China, in 2021–2023 - Pei, Rong; Zhang, Yulian; Jike, Chunnong; Yu, Gang; Su, Ling; Wang, Ju; Xiao, Lin; Wang, Yubing; Shen, Maogang; Liao, Jiayi; Zheng, Yifei; Hemelaar, Joris (Frontiers in Public Health, 2025)
IntroductionDespite expanded antiretroviral therapy (ART) in China, HIV transmission persists. Liangshan Prefecture is one of the areas in China most severely affected by HIV, with high levels of drug resistance. A deeper understanding of HIV-1 drug resistance can lead to improvements in current treatment policies.MethodsWe conducted an analysis of HIV drug resistance mutations (DRMs) among patients with treatment failure and people newly diagnosed with HIV in Liangshan Prefecture. 8,523 blood samples were collected from people living with HIV with treatment failure and newly diagnosed individuals in all 15 counties and two cities in Liangshan Prefecture between 2021 and 2023.Results43.0% of patients with treatment failure acquired HIV through the heterosexual route, followed by injecting drug use (38.7%), while newly diagnosed individuals mainly acquired HIV through the heterosexual route (86.7%). 95.6% of patients with treatment failure were infected with HIV-1 variant CRF07_BC and 2.7% with CRF08_BC, and newly diagnosed individuals were also main infected with HIV-1 variant CRF07_BC (90.9), followed by CRF08_BC (4.0%) and CRF01_AE (2.5%). The overall prevalence of acquired drug resistance (ADR) among patients with treatment failure was 57.4%. The overall prevalence of pre-treatment drug resistance (PDR) among newly diagnosed individuals was 23.9%. A high prevalence of ADR and PDR (especially high-level resistance) to efavirenz (48.0% vs. 11.1%) and nevirapine (49.6% vs. 11.4%) was found. The main non-nucleoside reverse transcriptase inhibitor (NNRTI)-associated ADR and PDR mutations were K103, V106, and V179. Our findings highlight age <18 years, injecting drug use, and initiation on NNRTI-based regimen as independent risk factors for HIV ADR development. We found minor variants as a risk factor for PDR, and CRF01_AE was associated with a higher risk than CRF07_BC for nucleoside reverse transcriptase inhibitor (NRTI) PDR.DiscussionGiven the high levels of NNRTI ADR and PDR, future clinical treatment plans should minimize the use of NNRTI-based regimens and should instead adopt alternative ART regimens more frequently.